Security and Architectural Issues for National Security Cloud Computing - Kim, Anya; McDermott, J; Myong Kang (2010 IEEE 30th International Conference on Distributed Computing Systems Workshops, 2010)
Security concerns with respect to cloud computing have impelled the private sector to suggest a hybrid cloud architecture consisting of private and public clouds. For national security purposes, we advocate a hybrid cloud model that consists of private, public and community clouds. The community clouds in this architecture are as defined by NIST, and will be used for inter-agency and community-of-interest (COI) information sharing and collaboration needs. The security requirements and characteristics of private and public clouds will not differ greatly from the private sector. However, while the architectural characteristics remain the same, we believe that national security community clouds will have different security features than the typical community cloud in order to support COI requirements. In this paper, we focus on the requirements and characteristics of national security community clouds that can meet the needs of COIs.